2014
DOI: 10.11604/pamj.2014.18.84.4586
|View full text |Cite
|
Sign up to set email alerts
|

Schwannoma of the urinary bladder: a case report

Abstract: Bladder schwannomas are exceedingly rare, benign or malignant, nerve sheath tumors that are most often discovered in patients with a known diagnosis of Neurofibromatosis type 1 (NF1). A few sporadic case reports of bladder schwannoma have been published in urologic, obstetric/gynecologic, and pathologic journals. We report a case of an isolated schwannoma of the urinary bladder. To our knowledge, this represents only the sixth case of benign schwannoma of the urinary bladder in a patient without von Recklingha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Its occurrence is lower the 0.1%. 2 The diagnosis of schwannoma is most often based on histology rather than on clinical presentation. Its differential diagnosis is usually transitional cell carcinomas, adenocarcinomas or squamous cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Its occurrence is lower the 0.1%. 2 The diagnosis of schwannoma is most often based on histology rather than on clinical presentation. Its differential diagnosis is usually transitional cell carcinomas, adenocarcinomas or squamous cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent follow-up showed the tumor regrowth and conservative treatment was chosen with regular follow-up ( 7 ). In addition, radiotherapy can also be used as an attempt ( 10 , 12 ). It has been reported that chemotherapy is invalid to extracranial schwannoma ( 9 ).…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…Isolated schwannomas have also been discovered in other areas such as the kidney and retroperitoneum but rarely in the bladder. 3 It occurs most commonly in the 4th to 6th decade of life. Bladder schwannomas may present with voiding and/or storage symptoms, flank pain or incontinence.…”
Section: Discussionmentioning
confidence: 99%